The effects of a maternal nursing competency reinforcement program on nursing students' problem-solving ability, emotional intelligence, self-directed learning ability, and maternal nursing performance in Korea: a randomized controlled trial - Sun-Hee Kim; Bo Gyeong Lee (Korean Society of Women Health Nursing, 2021)
Purpose The purpose of this study was to develop a maternal nursing competency reinforcement program for nursing students and assess the program's effectiveness in Korea. Methods The maternal nursing competency reinforcement program was developed following the ADDIE model. This study employed an explanatory sequential mixed methods design that applied a non-blinded, randomized controlled trial with nursing students (28 experimental, 33 control) followed by open-ended interviews with a subset (n=7). Data were analyzed by both qualitative and quantitative analysis methods. Results Repeated measures analysis of variance showed that significant differences according to group and time in maternal nursing performance; assessment of and intervention in postpartum uterine involution and vaginal discharge (F=24.04, p<.001), assessment of and intervention in amniotic membrane rupture (F=36.39, p<.001), assessment of and intervention in delivery process through vaginal examination (F=32.42, p<.001), and nursing care of patients undergoing induced labor (F=48.03, p<.001). Group and time improvements were also noted for problem-solving ability (F=9.73, p<.001) and emotional intelligence (F=4.32, p=.016). There were significant differences between groups in self-directed learning ability (F=13.09 p=.001), but not over time. The three themes derived from content analysis include "learning with a colleague by simulation promotes self-reflection and learning," "improvement in maternal nursing knowledge and performance by learning various countermeasures," and "learning of emotionally supportive care, but being insufficient." Conclusion The maternal nursing competency reinforcement program can be effectively utilized to improve maternal nursing performance, problem-solving ability, and emotional intelligence for nursing students.